The Portuguese Formal Social Support for Autonomy and Dependence in Pain Inventory (FSSADI_PAIN): A preliminary validation study. - Matos, M. (2013)
Objectives. Development and preliminary validation of a Portuguese measure of perceived Formal Social Support for Autonomy and Dependence in Pain (FSSADI_PAIN). Methods. One hundred and fifty-one older adults (88.1% women), between 56 and 94 years of age (M = 75.41; SD = 9.11), who attended one of the following institutions – day care centre (33.1%), nursing home (36.4%) and senior university (30.5%) – were recruited for this study. Along with the FSSADI_PAIN, participants filled out the Portuguese versions of the Brief Pain Inventory (Azevedo et al., 2007, Dor, 15, 6) and the Social Support Scale of Medical Outcomes Survey (Pais-Ribeiro & Ponte, 2009, Psicologia, Saude & Doença, 10, 163). Results. The factorial structure reflected the functions of perceived promotion of (1) dependence and (2) autonomy, showing good internal consistency (a > .70) and sensitivity indices. The FSSADI_PAIN showed good content, discriminant and criterion validity; it differentiated the perceptions of promotion of dependence/autonomy according to individual’s pain severity and disability, as well as the type of institution. Conclusions. These preliminary findings suggest that the FSSADI_PAIN is an innovative and promising measure of perceived formal social support adapted to pain-related contexts